‘It’s a delicate topic’: Stigma, capabilities and young people’s mental health in post-conflict Colombia - Sara Donetto; Shari Ortiz Baddan Sochandamandou; Maria Camila Garcia Duran; Philipp Hessel; Annie Zimmerman; Ricardo Araya Baltra; Fabio Idrobo (Global Public Health)
Young people in Colombia present high rates of mental health problems, to which the country’s history of armed internal conflict contributes in complex ways. Mental health services in Colombia are fragmented, inadequate, and difficult to access for many. Young people’s help-seeking is often hindered by mental health stigma and/or poor experiences with services. This paper presents a thematic analysis of qualitative data from a mixed-methods study aimed at developing and testing a mental health intervention for Colombian youths. We draw upon theoretical lenses from scholarly work on stigma and Sen’s ‘capabilities approach’ to inform our analysis of interviews and group discussions with staff and young people involved in the state-funded human capital building programme ‘Jovenes en Acción’ (JeA). By illustrating how study participants talked about stigma, vulnerability, mental health services organisation, and the challenges of discussing mental health topics in a learning environment, we illuminate aspects of mental health support and anti-stigma interventions that might need enhancing. In particular, we suggest that more emphasis on ‘community competencies’ as complementary to and interrelated with individual competencies would strengthen young people’s individual and collective resources for mental wellbeing while being in line with the sociocritical principles of existing human capital-enhancing programmes.